Burning Mouth Syndrome: An Enigmatic Disorder - Javali, MA (Kathmandu University Medical Journal, 2015)
Burning mouth syndrome (BMS) is a chronic oral pain or burning sensation affecting the oral mucosa, often unaccompanied by mucosal lesions or other evident clinical signs. It is observed principally in middle-aged patients and postmenopausal women and may be accompanied by xerostomia and altered taste. Burning mouth syndrome is characterized by an intense burning or stinging sensation, preferably on the tongue or in other areas of mouth. This disorder is one of the most common, encountered in the clinical practice. This condition is probably of multifactorial origin; however the exact underlying etiology remains uncertain. This article discusses several aspects of BMS, updates current knowledge about the etiopathogenesis and describes the clinical features as well as the diagnosis and management of BMS patients. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12498 Kathmandu University Medical Journal Vol.11(2) 2013: 175-178